High-risk Neuroblastoma in Young Adult and Long Term Survival with Multimodal Therapy: A Case Report - Amaylia Oehadian; Afiati Afiati; Martina Sung; Kevin Yonatan Budiman; Fransisca Fransisca (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To present a case of high-risk, stage four neuroblastoma in a 20-year-old woman who survived more than 21 months with the multimodal therapy.Methods: A case of high-risk, stage four neuroblastoma in a 20-year-old woman who survived more than 21 months with multimodal therapy is reported. The patient initially received neoadjuvant chemotherapy according to the Turkish Pediatric Oncology Group of Neuroblastoma, along with multiple doses of radiotherapy. After two cycles of induction chemotherapy, she successfully underwent tumor debulking surgery.Results: With the multimodal therapy, patient remains in complete remission state and stable disease of the remaining lesions is observed in this patient.Conclusions: Neuroblastoma is a rare disease in adults and associated with a high number of mortality. Early and accurate diagnosis and multimodality of treatments are important to achieve disease control. Long term follow up is necessary for such patients.